Tuam Cathedral, fourteenth-century choir, interior south wall, sedilia, jamb - O'Donovan, Danielle (My University, 2008)
Sedilia jamb, moulding from intrados comprises: (replica section) quirk, mitre, hollow, mitre, quirk, flat surface, roll, flat surface, quirk, keel, hollow, keel, quirk, flat surface, roll, flat surface, quirk, mitre, hollow, mitre, hollow, flat surface. The rolls here are very full and should be read as engaged shafts.
Sedilia
Keywords: mitre; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Late Medieval; roll moldings; keel moldings